Child care quality and children's cognitive and socio-emotional development: an Australian longitudinal study - Gialamas, A; Sawyer, M. G.; Sawyer, M; Mittinty, M. N.; Mittinty, M; Lynch, J; Zubrick, S. R.; Zubrick, S (My University, 2013)
There is growing evidence that high-quality non-parental child care can contribute to children’s learning, development and successful transition to school. Research examining the quality of child care and the effect on children’s development is not well documented outside the USA. We used data from the Longitudinal Study of Australian Children to examine the association between domain-specific aspects of child care quality at ages two to three and children’s cognitive (receptive vocabulary, literacy, maths proficiency) and socio-emotional development (internalising, externalising behaviours) at ages four to five and six to seven (n = 772–1136, depending on outcome). After extensive controls for parent, family and child background characteristics, higher quality relationships were associated with higher receptive vocabulary, literacy and maths scores and lower internalising and externalising problem behaviour scores at four to five and these effects although weaker, were still evident at ages six to seven. Activities in child care and provider/programme characteristics of care were not associated with children’s developmental outcomes.
Keywords: Child Development -- Cognitive; Child Care; Children -- Early childhood; Child Development -- Emotional; Childhood and child development; Child Development; Child Care; Children; Cognitive; Emotional; Early childhood; Childhood and child development